Optimización del crecimiento de helianthus annuus l. (girasol) para la fitoextracción de plomo, zinc y cadmio de relaves minero artesanal del caserío de zarumilla, pataz. - Lizarbe Asmat, Katherine Yelitza (2013)
In this study was assessed, by controlled trials, optimize growth of Helianthus annuus L. (sunflower), bioaccumulative species of heavy metals, by adding inorganic and organic conditioners to artisanal mining tailings for the phytoextraction of lead, zinc and cadmium. In total four treatments were tested of different proportions tailings - conditioner (100 - 0%, 75 - 25 %, 50 - 50 %, 25 - 75 %, respectively), with 6 replicates each, for periods of 30, 60 and 90 days by two seeding methods (direct and transplantation). Physicochemical analysis were performed at the treatments (pH, electrical conductivity, organic matter, available phosphorus and available potassium), it found growth parameters of sunflower (root length, stem length, number of leaves, and dry weight) and determined the concentration of Pb, Zn and Cd in the tailings and vegetables organs of sunflower. The results show that the sunflowers achieved to grow in treatments with added conditioner and accumulate in their tissues Pb, Zn and Cd; being affected the concentration of these metals, with respect to time, by the organic matter content of the treatments. The trials achieved, the method of direct seeding is the greatest amount of Pb, Zn and Cd concentrated, being the root the organ the highest bioaccumulation of these metals. Also, was observed that the best results are obtained in treatment 2 (75% of tailings and 25% conditioner).